2006
DOI: 10.1029/2006wr004931
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effective allocation of watershed management practices using a genetic algorithm

Abstract: [1] Implementation of conservation programs are perceived as being crucial for restoring and protecting waters and watersheds from nonpoint source pollution. Success of these programs depends to a great extent on planning tools that can assist the watershed management process. Herein a novel optimization methodology is presented for deriving watershed-scale sediment and nutrient control plans that incorporate multiple, and often conflicting, objectives. The method combines the use of a watershed model (SWAT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
116
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 185 publications
(119 citation statements)
references
References 16 publications
0
116
0
2
Order By: Relevance
“…Government agencies promote implementation of NPS pollution control practices by cost-sharing with land owners and farmers that is deemed as a field-by-filed approach [WilliaVeith et al, 2003]. Recent studies have shown that holistic watershed-scale strategies for targeted implementation of conservation practices could enhance environmental benefits gained from conservation expenditure [Arabi et al, 2006;Rao et al, 2007;Maringanti et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Government agencies promote implementation of NPS pollution control practices by cost-sharing with land owners and farmers that is deemed as a field-by-filed approach [WilliaVeith et al, 2003]. Recent studies have shown that holistic watershed-scale strategies for targeted implementation of conservation practices could enhance environmental benefits gained from conservation expenditure [Arabi et al, 2006;Rao et al, 2007;Maringanti et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Multiobjective optimization methods present an alternative approach that can effectively explore the tradeoffs between socioeconomic and environmental factors. While earlier studies utilized single-objective optimization approach for optimal allocation of conservation practices [WilliaVeith et al, 2003;Arabi et al, 2006], more recent efforts have focused on the development and application of multiobjective approaches [Maringanti et al, 2008;Jha et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations